Models and Studies of Aging: Executive Summary of a Report from the U13 Conference Series. Issue 3 (29th January 2019) - Hurria, Arti; Carpenter, Christopher R.; McFarland, Frances; Lundebjerg, Nancy E.; de Cabo, Rafael; Ferrucci, Luigi; Studenski, Stephanie A.; Barzilai, Nir; Briggs, Josephine P.; Ix, Joachim H.; Kitzman, Dalane W.; Kuchel, George A.; et al.
Abstract : The American Geriatrics Society convened a conference in Bethesda, Maryland, to explore models and studies of aging. This was the second of three conferences, supported by a U13 grant from the National Institute on Aging, to aid recipients of Grants for Early Medical/Surgical Specialists Transition to Aging Research (GEMSSTAR) in integrating geriatrics into their specialties. Recognizing that aging is the largest risk factor for multiple chronic diseases and age‐related loss of resilience, the conference organizers focused scientific sessions on how targeting age‐related mechanisms can delay, prevent, or reverse geriatric syndromes, age‐related chronic diseases, and loss of resilience. The rationale for studying models of aging as well as study designs, strategies, and challenges of studying human aging were reviewed. This article provides a summary of the full conference report, Models and Studies of Aging: Report from the U13 Conference Series, and summarizes key take‐home messages that were designed to support GEMSSTAR awardees in developing their research careers focused on aging research (see supplementary text for the full report). J Am Geriatr Soc 67:428–433, 2019.